(untitled) (JURNAL ADMINISTRASI PUBLIK, 2020)
There are still many people who deserve free health services can not receive assistance based on problems then this research aims to know the implementation of the policy of Indonesia healthy card in the public hospital Manembo District-Nembo Bitung This research is a qualitative research that is a type of research that gives an overview of the description of a situation on the object studied. The number of research informant 8 persons selected has the criteria for the information obtained useful for the research conducted The results showed that the benefits of healthy Indonesian cards are very perceived by the community especially for those who have been admitted to the General Hospital Manembo-Nembo district. Bitung. Quality of government apparatus in Bitung City is not fully able to support the implementation of policies or implementation of Indonesia Sehat card program because there are many complaints of people in the service when they are hospitalized or puskesmas, there is still discrimination in service by health workers. The structure and mechanism of procedure in implementing the Indonesian Healthy Card program goes well with the clear standard of work following the technical instructions and implementing organizations are well coordinated. Keywords: policy implementation, healthy Indonesia card